The Contributions, Challenges and Potential of Islamic Finance in Relation to International Trade: (Sumbangan, Cabaran dan Potensi Kewangan Islam dalam Perdagangan Antarabangsa) (Kanun: Jurnal Undang-undang Malaysia, 2017)
This paper looks at the development, contributions, challenges and potential of the Islamic financial system in the context of international trade. The qualitative method was applied to analyze earlier literature and publications, including the policies of the government and universities. The analysis finds that the Islamic financial system is developing at a consistent and rapid rate at national and global level, demonstrating its competitiveness and added value. However, Islamophobia and bias towards Islam is spreading rapidly without control and this will negatively affect the global Islamic financial system. This paper highlights the contributions and challenges currently faced by the system.Keywords: Islamic finance,Islamic banking, laws, syariah, Islamophobia